Peningkatan Kemampuan Critical Thinking dan Collaboration Siswa Abad 21 Pada Materi Banjir Melalui Model PBL - Silvia, Neng Ineu; Sujana, Atep; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2019)
Critical thinking can encourage students to solve problems in a collaborative way or work with peers. The purpose of the study was to determine the improvement of critical thinking and collaboration students by using the Problem Based Learning modelin flood material. This study uses a quasi-experimental method and nonequivalent control group design research design using critical thinking instruments and collaborative questionnaires. The population of the study was all students in class V of Cimalaka Subdistrict with a sample of class V students of SDN Cilimbangan experimental class and fifth grade students of SDN Citimun II control class. The conclusions of this study: 1) Science learning using the Problem Based Learning model can significantly improve students critical thinking skills, 2) Science learning using the Problem Based Learning model is better at improving students critical thinking skills than using expository learning. 3) Science learning using the Problem Based Learning model can improve students collaborative abilities compared to expository learning.